Clozapine and paliperidone palmitate antipsychotic combination in treatment-resistant schizophrenia and other psychotic disorders: A retrospective 6-month mirror-image study. Issue 1 (2020) - Bioque, Miquel; Parellada, Eduard; García-Rizo, Clemente; Amoretti, Sílvia; Fortea, Adriana; Oriolo, Giovanni; Palau, Pol; Boix-Quintana, Ester; Safont, Gemma; Bernardo, Miquel
Abstract: Background: Around 30% of patients with schizophrenia are considered treatment resistant (TRS). Only around 40% of TRS patients respond to clozapine. Long acting injectable antipsychotics could be a useful augmentation strategy for nonresponders. Methods: We conducted a multicenter, observational, naturalistic, retrospective, 6-month mirror-image study to evaluate the efficacy and tolerability of clozapine and paliperidone palmitate association in 50 patients with TRS and other psychotic disorders. Clinical outcomes and side effects were systematically assessed. Results: Six months after starting the combined treatment, participants showed a significant relief of symptoms, decreasing the Brief Psychiatric Rating Scale total score from 18.32 ± 7.71 to 7.84 ± 5.16 ( p < 0.001). The number of hospitalizations, the length of hospital stays and the number of visits to emergency services also decreased, while an increase of the functionality was observed (Personal and Social Performance total score increased from 46.06 ± 118.7 to 60.86 ± 18.68, p < 0.001). There was also a significant decrease in the number and severity of side effects with the combination therapy, decreasing the Udvalg for Kliniske Undersogelser total score from 10.76 ± 8.04 to 8.82 ± 6.63 ( p = 0.004). Conclusions: This study provides the first evidence that combining clozapine with paliperidone palmitate in patients with TRS and other psychotic disorders could be effective and safe, suggesting further research with randomized controlled trials of augmentation strategies for clozapine nonresponder patients. Policy Significance Statement: Patients with psychotic disorders such as schizophrenia show a variable response to antipsychotic treatments. Around 30% of patients are considered treatment resistant, indicated by insufficient symptom control to at least two different drugs. In these resistant cases, clozapine should be indicated, as it has shown to be superior to other options. However, only 40% of patients respond to clozapine, being necessary to establish which treatments could best potentiate clozapine action. Combining clozapine with long acting injectable antipsychotics, and particularly paliperidone palmitate, could be a useful strategy. We conducted a multicenter study of 50 patients with treatment-resistant schizophrenia and other psychotic disorders comparing the efficacy and tolerability in the 6 month-period prior and after starting the clozapine and paliperidone palmitate association. Our study suggests that this combination could be effective and safer, laying the groundwork for future clinical trials with this combination.